Cleaning device - YAN GUIXIANG (2024)
The utility model discloses a cleaning device applied to a scrubber and other similar devices, which comprises a main body part and a dust suction port arranged at the bottom of the main body part, a rolling brush assembly is arranged at the dust suction port and comprises a first rolling brush body and a second rolling brush body, the second rolling brush body is arranged at the front end of the first rolling brush body, and the second rolling brush body is arranged at the front end of the second rolling brush body. The diameter of the second rolling brush body is smaller than that of all the first rolling brush bodies, and the lowest working face of the second rolling brush body is lower than that of all the first rolling brush bodies. And by arranging the second rolling brush body with the front small pipe diameter, cleaning treatment on positions such as wall corners which are difficult to clean is achieved, and the overall usability is improved. 本实用新型公开了一种应用于洗地机等类似装置的清洁设备，包括主体部和设置于主体部底部的吸尘口，所述吸尘口处设置有滚刷组件